“Todos iguais, mas uns mais iguais que outros”: Relações de gênero na carreira universitária do Paraná - Machado, Roseli de Oliveira (2023)
This work discusses gender relations and their expressions in the academic career that takes place in the Higher Education System of the state of Paraná, between the years 2011 and 2020. From the gender perspective of Joan Scott (1995), it analyzes the composition of the professor staff, the development in the career, the occupation of positions of scientific prestige, and access to academic management functions in university structures, by women professors at the seven state universities that make up the mentioned system. The study consists of two stages with sources of information and instruments for data collection and analysis. The first phase, of a quantitative nature, is carried out from the construction of a repository containing 77 variables related to the effective staff of the system, analyzed using four logistic and linear regression models. The second phase, of a qualitative nature and undertaken by oral history, has ten interviews with professors belonging to state universities. Based on quantitative and qualitative data, three different career perspectives are analyzed - profile of participation in institutionalized job classes, academic-scientific influence and political-administrative influence, with four themes running through these analyzes - gendered choices, sexual division of labor, sexism and academic illness. The analysis of the profile of the professor staff reveals a slight male predominance and the existence of the sexual division of labor, manifested by the horizontal concentration in the system. Furthermore, there are strong indications of vertical concentration in the analyzed institutions, marked by the presence of a career funnel, capable of delaying female entry into the upper classes of the institutionalized professor position and able of making the levels of greater scientific and political-administrative prestige in university structures almost inaccessible to women. It is concluded that, despite guarantees of equality in hiring and development, due to legal provisions, the academic-university career in the state of Paraná is not exempt from important gender imbalances. Given this, it is possible to infer that, notwithstanding its indisputable role as a catalyst for economic and social development and its vanguard position, the university acts strongly as a reproductive entity of the social order.